I’m More Prosocial than Others: Narcissism Facilitates Prosocial Behavior in Public Situations - Yining Song; Qiong Chen; Ping Ren; Jing Ma; Caina Li (Behavioral Sciences)
Although narcissism consistently predicts maladaptive behaviors, the relationship between narcissism and prosocial behavior remains controversial due to the paradoxical nature of narcissism. In three studies, we investigated the roles of situational and motivational factors in the link between narcissism and prosocial behavior. In Study 1 (n = 932), a questionnaire survey revealed that trait narcissism positively predicted prosocial behavior tendencies only in public situations as opposed to anonymous situations. In Study 2 (n = 200) and 3 (n = 170), we manipulated individuals’ state narcissism through story-based primes and measured prosocial behavior via actual monetary donations. Both Studies 2 and 3 consistently demonstrated that participants in the state narcissism group exhibited greater prosocial behavior in public situations compared to anonymous ones. Furthermore, the findings of Study 3 indicated that the increased prosocial behavior observed in public situations could be attributed to heightened self-enhancement. These findings contribute to a more nuanced understanding of the relationship between narcissism and prosocial behavior.